The Impact of TikTok Marketing on Consumer Motivation and Purchase Decisions for Tourism Products in Labuan Bajo - Widilestari, Christine; Masriah, Masriah; Nugroho, Agung Yuliyanto; Putrianti, Flora Grace; Anshoriyah, Sofiyatul (International Journal of Economics (IJEC), 2025)
This study aims to describe the impact of social media, specifically TikTok, on advertising and marketing in Labuan Bajo's tourism industry. The study was conducted in Labuan Bajo with approximately 100 respondents, and data was collected and analyzed quantitatively to assess the influence of social media on consumer behavior and purchasing decisions. This study examines the effectiveness of TikTok as a promotional and marketing tool in encouraging consumers to purchase tourism products in Labuan Bajo. The findings indicate that TikTok is a viable promotional medium that can have a significant impact on consumer decision-making when it comes to culinary products. The use of this social media platform has a notable influence on the tourism industry in Labuan Bajo